The evaluation of pulmonary vein isolation and wide-area left atrial ablation to treat atrial fibrillation in patients with implanted permanent pacemakers: the Previously Paced Pulmonary Vein Isolation Study. Issue 13 (18th May 2010) - Veasey, R A; Silberbauer, J; Schilling, R J; Morgan, J M; Paul, V; Furniss, S S; Sulke, N
Abstract : Background: The practise of catheter ablation for atrial fibrillation (AF) is increasing rapidly and is recommended as the treatment of choice in many patient subgroups. At present, the efficacy of this procedure has been assessed by means of electrocardiographic recording, intermittent Holter monitoring and evaluation of patient symptoms. We sought to evaluate the true efficacy of this procedure in patients with sophisticated permanent pacemakers capable of continuous long-term cardiac rhythm monitoring. Methods: Twenty-five patients (aged 63.7 (9.4), 20 men), seven with persistent AF and 18 with prolonged paroxysmal AF, underwent a mean of 1.7 AF ablation procedures. All the patients had previously been implanted with a pacemaker or atrial defibrillator device. Data were downloaded from the device Holter before catheter ablation and at 2, 4, 6 and 8 months postprocedure(s). The primary outcome measure was AF burden. The secondary outcomes were patient symptom and quality-of-life measures. Results: Initial AF burden was 43.8 (35.5)%. After catheter ablation(s), this was significantly reduced at 2 months to 23.8 (35.4)% (p=0.023), at 4 months to 21.4 (34.1)% (p=0.008), at 6 months to 14.5 (28.1)% (p=0.002) and at 8 months to 15.0 (29.4%) (p=0.003). Only nine (36%) of 25 patients demonstrated no recurrence of arrhythmia during follow-up completion, consistent with a long-term cure. Quality-of-life indices showed significant improvement after ablation. Conclusions: Catheter ablation for AF significantly improves patient symptoms and reduces AF burden after long-term beat-to-beat monitoring by implanted cardiac pacemaker and defibrillator devices. However, AF recurrence is common after these procedures.